Cloning, identification, and functional analysis of foxl2 gene and its expression after 17β‐estradiol (E2) treatment in Dabry’s sturgeon, Acipenser dabryanus - Hu, Yacheng; Tan, Ruihua; Shu, Tingting; Chu, Zhong; Wang, Haoran; Chen, Yining; Zhu, Xin; Li, Yang; Wang, Binzhong; Guo, Baifu; Wang, Runqiu; Qu, Huantao; et al. (Frontiers in Marine Science, 2024)
The study focuses on the critically endangered Dabry’s sturgeon (Acipenser dabryanus), a species on the brink of extinction in the wild. This research investigates the role of the Forkhead box protein L2 (foxl2) in the gonadal development and differentiation of this species. The foxl2 gene, known for its role in various physiological processes, including sexual maturation, is hypothesized to play a significant role in the sex differentiation of Dabry’s sturgeon. This study cloned the full-length cds sequence of the foxl2 gene and analyzed its expression across various tissues, focusing on its response to estradiol treatment. Our findings indicate that foxl2 is predominantly expressed in ovaries and shows a dose-dependent response to estradiol, suggesting its potential role in ovarian differentiation. This research underscores the importance of foxl2 in understanding reproductive biology and offers a foundation for future conservation strategies.